2020
DOI: 10.1074/jbc.ra119.012072
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA levels of heat shock factor 1 are regulated by thermogenic signals via the cAMP-dependent transcription factor ATF3

Abstract: Heat shock factor 1 (HSF1) regulates cellular adaptation to challenges such as heat shock and oxidative and proteotoxic stresses. We have recently reported a previously unappreciated role for HSF1 in the regulation of energy metabolism in fat tissues; however, whether HSF1 is differentially expressed in adipose depots and how its levels are regulated in fat tissues remain unclear. Here, we show that HSF1 levels are higher in brown and subcutaneous fat tissues than in those in the visceral depot and that HSF1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The highest scoring GO category was negative regulation of Ras signal transduction, indicating that high Ras activity leads to high HSR activity. This is consistent with a previous study showing an inverse correlation between the HSR and the Ras/PKA-inhibited Msn2/4 pathway ( Brandman et al, 2012 ) and studies concluding that the PKA activity induces the HSR ( Murshid et al, 2010 ; Verma et al, 2020 ) The lowest scoring categories included mitochondria and translation, consistent with results of a previous HSR screen ( Brandman et al, 2012 ). Knockdowns of genes involved in vacuolar acidification, a process important for many cellular activities such as protein sorting and pH maintenance ( Yamashiro et al, 1990 ) as well as regulation of the HSR ( Triandafillou et al, 2018 ) also caused a significant downregulation of the HSR.…”
Section: Resultssupporting
confidence: 92%
“…The highest scoring GO category was negative regulation of Ras signal transduction, indicating that high Ras activity leads to high HSR activity. This is consistent with a previous study showing an inverse correlation between the HSR and the Ras/PKA-inhibited Msn2/4 pathway ( Brandman et al, 2012 ) and studies concluding that the PKA activity induces the HSR ( Murshid et al, 2010 ; Verma et al, 2020 ) The lowest scoring categories included mitochondria and translation, consistent with results of a previous HSR screen ( Brandman et al, 2012 ). Knockdowns of genes involved in vacuolar acidification, a process important for many cellular activities such as protein sorting and pH maintenance ( Yamashiro et al, 1990 ) as well as regulation of the HSR ( Triandafillou et al, 2018 ) also caused a significant downregulation of the HSR.…”
Section: Resultssupporting
confidence: 92%
“…Total RNA was extracted with TRIzol (Invitrogen), according to procedures described previously (Verma et al, 2020), from iWAT, eWAT, and BAT, liver, brain, and muscle tissues of 17‐month‐old mice, after three months of treatment with either a control diet or a diet containing Rosi. RNA was reverse transcribed into cDNA (First Strand cDNA Synthesis Kit, Roche), according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted with TRIzol (Invitrogen), according to procedures described previously (Verma et al, 2020), from iWAT,…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that HSF1 is induced by cold exposure and agents that increase cAMP levels ( 31 ). Furthermore, our studies have demonstrated that HSF1 plays a key role in the regulation of thermogenic tissues via induction of the expression of the metabolic coactivator PGC1α.…”
Section: Resultsmentioning
confidence: 99%